Prevalence of non-nutritive sucking habits and its relation with anterior open bite in children seen in the Odontopediatric Clinic of the University of Pernambuco - Magalhães,Luiza do Nascimento Cezar (2012)
OBJECTIVE: The aim of this work was to establish the prevalence of non-nutritive sucking habits (pacifier and/or digit sucking) and to assess its relation with anterior open bite. METHODS: The sample consisted of 980 records of children of both genders, with ages between 3 and 12 years, who were treated at the Pediatrics Clinic of the University of Pernambuco (FOP/UPE), from February 2000 trough December 2005, both sexes. Pearson's Chi-square test at 5% level of significance was used for statistical assessment. RESULTS: It was observed that 17,7% of the sample had some habit at the moment of the anamnesis (9,6% of digit sucking habit, 8,8% of pacifier sucking habit and 0,7% of both habits) and that the prevalence of open bite was 20,3%. The prevalence of sucking habits in girls was much higher than in boys (22,6% and 12,9%, respectively) and this difference was statistically significant (p = 0,000). A correlation between habits and open bite was proved statistically (p = 0,000): Children with sucking habits had 8 times more chances of developing anterior open bite. CONCLUSIONS: Anterior open bite was associated to the presence of non nutritive sucking habits; sucking habits were more prevalent in girls and in children between three and six years of age.